Pengaruh Karakteristik Pemerintah Daerah dan Faktor Keuangan terhadap Kondisi Financial Distress di Indonesia - Elfiyana Elfiyana; Fefri Indra Arza (Jurnal Eksplorasi Akuntansi, 2022)
This study aims to determine the effect of Regional Government Characteristics (Regional Financial Independence, Degree of Decentralization, and Population) and Financial Factors (Efficiency Ratio, Growth Ratio, and Effectiveness Ratio) on financial difficulties in Regency/City local governments in Indonesia in 2017-2019. . This study uses secondary data from BPK and BPS. The sampling technique used is a simple random sampling technique. So that obtained a sample of 170 districts and 54 cities per year. Data analysis is multiple linear regression analysis. This study found that (1) regional financial independence had a significant positive effect on financial distress, (2) the degree of decentralization had a significant negative effect on financial distress, (3) the population had a significant negative effect on financial distress, (4) the efficiency ratio had a significant positive effect on financial distress, (5) the growth ratio has a positive and insignificant effect on financial distress, (6) the effectiveness ratio has a positive and significant effect on financial distress